The Nagoya Protocol on the use of genetic resources:: one embodiment of an endless discussion - Aubertin, Catherine; Filoche, Geoffroy (Sustainability in Debate, 2011)
The purpose of this article is to highlight the process of negociation of the Nagoya Protocol on the use of genetic resources, adopted in october of 2010. While providing an overview of the myths and realities of biodiversity exploitation, it discusses how and why the arguments used by developing and developed countries were finally conciliated, resulting in a new international legal framework. The article shows wether the Protocol manages to implement Convention on Biological Diversity and to be consistent with relevant international law (on intellectual property for instance). It also aims at assessing if the Protocol is likely to reduce the everlasting gap between the legal concepts built by « biodiplomacy » and the actual needs and practices of scientists and companies. It finally estimates the impacts on the already existing frameworks, focusing on the Brazilian experience.